The Role of Competitive Advantage as a Mediator of the Influence of Financial Aspects, Human Capital, and Innovation Capability on the Business Performance of SMEs (Empirical Study of SMEs in Manokwari Regency) - Yertas, Maria; Ansar, Ansar; Gunawan, Gunawan; Kurniawaty, Kurniawaty (Green Publisher Indonesia, 2024)
This research aims to analyze the direct and indirect influence of financial aspects, human capital, innovation capabilities and competitive advantage on the performance of MSME businesses in Manokwari Regency. This type of research is quantitative research using Structural Equation Modeling (SEM) analysis with the AMOS program version 25. The research population is all MSMEs in Manokwari district, totaling 1344 people. The sample in this research was 230 MSMEs. Data collection was carried out through distributing questionnaires online and offline. The research results show that the direct relationship between financial aspects, human capital, innovation capability has a positive and significant effect on competitive advantage and business performance. Competitive advantage has a positive and significant effect on business performance. For indirect relationships, financial aspects and human capital have a significant effect on business performance through competitive advantage, while innovation capability does not have a significant effect on business performance through competitive advantage.